LANGUAGE SPACE OF NEURAL NETWORKS: FEATURES AND DIFFERENCES FROM NATURAL LANGUAGE - Natalia B. Egorchenkova; Olga V. Korobova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. Modern society is developing in a world of information overload and digitalization, which has led to a need for artificial intelligence (AI) to help analyze and process information more efficiently. Most AI models use natural language processing, and while they can imitate human speech, they generate texts based on templates set by humans. This creates an online language space that is unique to AI, with its own characteristics due to its isolation from human interaction.